Designing Framework of Electronic Continued Professional Development (E-CPD) for Teachers - Rafiza, A.R.; Yusop, F.D.
This paper discusses on designing framework of virtual training for teachers namely electronic Continued Professional Development (e-CPD). The discussion contributes to the professional development of teachers in applying virtual training to augment their understanding of their teaching according to specialization. The paper also presents the virtual teaching and learning platform such as Frog Virtual Learning Environment (VLE) initiated by the Malaysia Ministry of Education. E-CPD was thus designed in conjunction for teachers’ Continued Professional Development via a virtual environment. E-collaboration activities in the virtual training are also highlighted. Predominantly, the paper presented the development of e-CPD design framework which is essentially useful and recommended for future application in designing virtual training for technical skills.